Facial and skincare service system - Low, Chia Hui (2023)
Skin care management is paramount to ensure the clinic's management is smooth and manageable, as well as the first impression from the customer. Additionally, good management will ease the clutter and look professional to the customer. First impressions and trust from the customer are crucial for all businesses because the customer is the person that purchases the service and product. Running a Skincare Clinic is not just helping the customer feel beautiful after receiving the treatment. It is also about the trust gained from the customer. It is undeniable that clinic management is challenging to the clinic staff, whether in outpatient clinics, aesthetics clinics, dental clinics, or other clinics that are available in the market. This is because the problem of the patient is traditionally diagnosed by manual detecting and verifying, which is unsatisfying as the traditional diagnosis entirely depends on the professional skills and knowledge of the specialist in the skin care centre. The skin care management system is to solve the traditional way of diagnosing a patient's skin problem, which is subjective, requires great physical effort, and is time-consuming. Besides, the system also helps to encourage communication between the skincare specialist and the patient via online appointments. The proposed system is also designed to give flexibility to the staff and patient in concern of skincare service while using the system where they can use the mobile application. The system will use skin classification to replace the conventional way of diagnosis, which can give the specialist a better understanding of the patient's problem and provide appropriate feedback and guidance to the patient. Besides, the system allows online consultation, which enables the patient to reach the specialist in the skin care centre without physically going to the clinic. Other than that, the patient can make their appointment by using the system which is more flexible and convenient for both staff and patient because they do not require to negotiate the time to match with each other. The solution of this project is to improve the communication between the specialist and the patient to deliver feedback on the skin problem faced by the patient through online platform. The combination of video call plugin, TensorFlow Lite, Cloud Firestore Database and Flutter mobile application that able to manage the patient consultation and diagnose the skin condition of the patient is the aim of this project. The project has successfully fully completed with the features that allow the staff and patient to communicate using video call, manage the appointment booking, acne classification for acne type, and view the consultation history.